PENGARUH STRUKTUR KEPEMILIKAN, PROFITABILITAS, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2014) - Rizki Widya Puspitaningsih; Hotman Tohir Pohan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
The purpose of this study is to examine the effect of ownership structure, profitability, firm size, and firm age on Corporate Social Responsibility disclosure. Sample consists of 87 manufacturing firms in Indonesia Stock Exchange in 2014. Multiple regression test is used to test hypothesis developed in this study. Result of this study show that firm size has significantly positive influence on CSR disclosure, whereas ultimat ownership has significantly negative influence on Corporate Social Responsibility disclosure. Foreignt ownership, blockholder ownership, profitability, and firm age, on the other hand, do not have significant influence on CSR disclosure